Global change‐driven effects on dissolved organic matter composition: Implications for food webs of northern lakes - Irena F. Creed; Ann‐Kristin Bergström; Charles G. Trick; Nancy B. Grimm; Dag O. Hessen; Jan Karlsson; Karen A. Kidd; Emma Kritzberg; Diane M. McKnight; Erika C. Freeman; Oscar E. Senar; Agneta Andersson; et al. (Global Change Biology, 2018)
Northern ecosystems are experiencing some of the most dramatic impacts of global change on Earth. Rising temperatures, hydrological intensification, changes in atmospheric acid deposition and associated acidification recovery, and changes in vegetative cover are resulting in fundamental changes in terrestrial–aquatic biogeochemical linkages. The effects of global change are readily observed in alterations in the supply of dissolved organic matter ( DOM )—the messenger between terrestrial and lake ecosystems—with potentially profound effects on the structure and function of lakes. Northern terrestrial ecosystems contain substantial stores of organic matter and filter or funnel DOM , affecting the timing and magnitude of DOM delivery to surface waters. This terrestrial DOM is processed in streams, rivers, and lakes, ultimately shifting its composition, stoichiometry, and bioavailability. Here, we explore the potential consequences of these global change‐driven effects for lake food webs at northern latitudes. Notably, we provide evidence that increased allochthonous DOM supply to lakes is overwhelming increased autochthonous DOM supply that potentially results from earlier ice‐out and a longer growing season. Furthermore, we assess the potential implications of this shift for the nutritional quality of autotrophs in terms of their stoichiometry, fatty acid composition, toxin production, and methylmercury concentration, and therefore, contaminant transfer through the food web. We conclude that global change in northern regions leads not only to reduced primary productivity but also to nutritionally poorer lake food webs, with discernible consequences for the trophic web to fish and humans.